2010
DOI: 10.1029/2009gl042359
|View full text |Cite
|
Sign up to set email alerts
|

Coincident reflection images of the Gulf Stream from seismic and hydrographic data

Abstract: [1] The development of seismic oceanography requires direct comparison of seismic data to high-resolution oceanographic measurements over long horizontal scales. Here, we compare multichannel seismic (MCS) reflection images to 300 km of spatially-coincident, high-resolution (<1 km) expendable bathythermograph (XBT) surveys that were collected near a frontal region of the Gulf Stream. Fronts, eddies, tendrils, and interleaving were among the features identified in both data sets. In some cases, identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…One possible explanation for the feature is the strongly depressed isotherms/isopycnals (distinct water boundaries; temperature profiles with only negative gradients, not shown here), rather than the water boundaries of a cold tongue wrapping around the warm eddy as reported by Mirshak et al . [].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for the feature is the strongly depressed isotherms/isopycnals (distinct water boundaries; temperature profiles with only negative gradients, not shown here), rather than the water boundaries of a cold tongue wrapping around the warm eddy as reported by Mirshak et al . [].…”
Section: Discussionmentioning
confidence: 99%
“…While subsurface eddies (mostly Meddies) have been frequently studied using the seismic method [e.g., Biescas et al, 2008;Menesguen et al, 2012;Pinheiro et al, 2010], only two surface anticyclonic eddies have been briefly reported. One is a joint oceanographic and seismic survey by Mirshak et al [2010]. They presented a robust view but simple description of a surface eddy in the Gulf Stream region [Mirshak et al, 2010].…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflection coefficients were computed for the seismic frequency range 50–500 Hz, using equation and following the method detailed in section 3. Results plotted in Figure b show that the thermocline reflection coefficients vary between −87 and −59 dB, and span the range of the typical reflectivity of oceanographic structures [e.g., Holbrook et al ., ; Mirshak et al ., ]. These reflection coefficients are low compared to those typically found in the solid Earth (−40 dB) and at the seafloor (−20 to −8 dB) [ Telford et al ., ].…”
Section: Seismic Imaging Of Shallow Oceanographic Structuresmentioning
confidence: 99%
“…The physical basis for seismic oceanography has been well established by several studies that combined seismic surveys with simultaneous in situ measurements of temperature, salinity, and density (Nakamura et al 2006;Nandi et al 2004;Sallar es et al 2009): weak, but clear, reflections from within the water column come from vertical changes in (primarily) sound speed and (secondarily) density. Over the past few years, numerous studies have demonstrated the ability of seismic imaging to detect and map major features in the ocean, including fronts (Holbrook et al 2003;Mirshak et al 2010;Sheen et al 2009), internal waves (Holbrook and Fer 2005;Krahmann et al 2008), eddies and warm-core rings (Biescas et al 2008;Ruddick et al 2009;Yamashita et al 2011), thermohaline staircases (Biescas et al 2010;Fer et al 2010), lee waves (Eakin et al 2011), and internal tide beams ). SO has several unique capabilities, including the ability to image fine structure over large sections of the ocean and to full ocean depth, provided that sufficient fine structure is present to produce reflections.…”
Section: Introductionmentioning
confidence: 99%